Somatic Embryogenesis From Immature Male Flowers Of Banana (Musa Spp. Cv. Rastali) - Mohd Zainol Azlin, Aini (2008)

(untitled)
This study was carried out with the main objective of establishing a plant regeneration system through somatic embryogenesis in Musa spp cv. Rastali. The study included induction of embryogenic callus and somatic embryos from immature male flowers, initiation of cell suspension cultures from the embryogenic callus and somatic embryos, proliferation of somatic embryos from the embryogenic cell suspension followed by embryo maturation and germination. In the study on embryogenic callus induction from immature male flowers of banana cv. Rastali, the effect of 2,4-dichlorophenoxyacetic acid (2,4-D) and different flower cluster positions on the embryogenic callus formation was determined. Various concentrations of 2,4-D (0, 1, 2 and 4 mg/L) were incorporated into M1 medium consisting of MS medium, 1 mg/L IAA, 1mg/L NAA, 30 g/L sucrose and 7 g/L agarose. The levels of 2,4-D affected the embryogenic callus initiation and somatic embryo formation in cv. Rastali. The highest percentage of embryogenic callus formation (53.9 %) was obtained on treatment with 2 mg/L 2,4-D in cv. Rastali for all flower cluster positions assessed. The effect of flower cluster positions on percentage of embryogenic callus formation showed the highest percentage (48.4 %) was from flower cluster position 8 in cv. Rastali. Interaction between the different flower cluster positions and 2,4-D concentrations produced the highest percentage of embryogenic callus formation (83.8 %) from flower cluster position 8 on treatment with 2 mg/L 2,4-D in cv. Rastali. After six months on the callus induction medium, calli varying from yellowish, creamy to white were formed. A positive embryogenic response was shown by the appearance of individual somatic embryos amongst the callus produced on 2 and 4 mg/L 2,4-D and this indicated an ideal callus. The initial phase of cell suspension establishment comprised of a mixture of cell aggregates and heterogenous cells that varied from embryogenic cells, nonembryogenic cells and elongated cells. The suspension cultures were refreshed monthly to improve the suspension quality and to obtain homogeneous embryogenic cell cultures. After a duration of one month, with agitation of the suspension culture, attached embryogenic cells broke free from the cell aggregates. Cells stained with fluorescein diacetate (FDA) fluoresced bright green when observed under a microscope with UV attachment indicating the cells were viable. It offers a quick visual assessment on percentage of cell viability. Meanwhile, Evan’s blue staining was also used to check the cell viability to complement the FDA assesment. When cells were treated with dilute (0.025 %) solution of Evan’s blue, intact and viable cells remained unstained whilst damaged cells took up the stain. The growth of suspended cells in S1 and S2 media over five subcultures showed a sporadic pattern. S1 medium consisted of half strength MS macronutrients, MS micronutrients, Dhed’a Vitamins, 10 mg/L ascorbic acid, 1.1 mg/L 2,4-D, 0.25 mg/L zeatin and 20 g/L sucrose, while S2 medium consisted of MS medium, 1 mg/L biotin, 1 mg/L 2,4-D, 99 mg/L glutamine, 100 mg/L malt extract (Sigma) and 44 mg/L sucrose. Cell growth was determined by counting cells using a haemocytometer. Highest cell count of 77 per ml was attained at subculture 2 in S2 medium while in S1 medium cells reached their highest growth rate of 75 per ml at subculture 5. Microscopic observation of the cell suspension in liquid S1 medium at the third subculture showed cells with small, distinct and voluminous nucleus as well as dense cytoplasm. In the meantime, closely attached cells with compact cytoplasm; mainly composed of embryogenic cells were observed in liquid S2 medium before sieving at the second subculture. Sieving out the elongated and vacuolated cells generated uniform and single meristematic cells in the medium, producing embryogenic cell suspensions that were less heterogeneous. After three months, with sieving and subculture, Musa sp. cv. Rastali produced a very fine, light yellow embryogenic suspension culture most suitable for embryo maturation and germination study. In the final stage after the fifth subculture, the embryogenic cell suspensions were transferred into MS liquid medium without hormone and showed formation of globular somatic embryos. Within one month after placing 1 mL of embryogenic cell suspension (ECS) onto a filter paper placed on M3 medium containing SH salts, MS vitamins, 1 mg/L biotin, 0.05 mg/L zeatin, 0.1 mg/L kinetin, 45 g/L sucrose, 10 g/L lactose, 100 mg/L glutamine, 230 mg/L proline, 0.2 mg/L NAA, 0.14 mg/L 2iP, 100 mg/L malt extract and 3 g/L phytagel, clusters of smooth globular to polar shaped somatic embryos creamy white in colour appeared. Such clusters of globular somatic embryos with hyaline protuberances formed many cell lines that allowed the selection of high quality lines. The creamy-like globular structures were transferred in clumps onto M4 germination medium consisting of MS macronutrients, MS micronutrients, MS Fe EDTA, Morel and Wetmore modified vitamin, 0.2 mg/L IAA, 30 g/L sucrose, 2 g/L phytagel and supplemented with different concentrations of BAP (0, 0.1, 0.5, 1.5 and 2.0 mg/L). After a duration of two months on the M4 germination medium, radicles and hairy roots emerged from the somatic embryos. A month later, development of the whitish radicles from the globular somatic embryos became prominent followed by the formation of greenish plumules. The radicles elongated into roots and the greenish plumules developed into shoots. Treatment with 0.5 mg/L BAP gave the highest regeneration percentage of 8.9 % compared to the control at 2.3 %. BAP concentrations of more than 0.5 mg/L resulted in stunted growth of plantlets and a decrease in the regeneration percentage. Plantlets obtained were transferred to hormone-free MS medium and placed in light condition for formation of chloroplasts and further growth of the shoots and roots. Histological study clearly showed the shoot and root development from somatic embryos of Musa sp. cv. Rastali. The shoot arised from in between the leaf primordia that were attached to the mother tissue. The shoot apex arrangement could be clearly seen through lateral section of the same specimen. The root portion was easily detached during sectioning nevertheless it was clearly evident in a separate histological section. The presence of shoot and root poles in the histological observation confirmed the bipolar nature of the somatic embryos.